The earth atlas - Van Rose, Susanna; Bonson, Richard (New York : Dorling Kindersley, 1994)
A visual guide to the earth's varied landscapes. Offers amazing facts and information about the earth's physical features around the globe.
Includes index.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
6.5.
6.5
Keywords: Children's atlases; Geology -- Maps for children; Physical geography -- Maps for children; Atlases; Atlases; Geography -- Atlases; Geology -- Atlases